KAJIAN KOMPOSISI MEDIA TUMBUH DAN PUPUK SAMPAH KOTA TERHADAP PRODUKTIVITAS BAWANG MERAH DENGAN TEKNIK VERTIKULTUR - Fathurrahman, Fathurrahman (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
Technological and industrial advancements and the rapid increase in population, gradually changing the function of agricultural land into housing and industrial complexes. Overcoming the reduction of agricultural land, efforts made by farming vertically or verticulture methods.Shallots are an important vegetable commodity for the community, because of their high economic value and nutritional content. To reduce imports, it is necessary to increase production and quality of shallots through intensification and extensification. The purpose of the study was to determine the effect of the composition of the growing media, the effect of the dose of organic fertilizer in municipal waste, and its interaction with the productivity of shallots with verticulture cultivation techniques.The study was conducted in the experimental area of ​​the Faculty of Agriculture, UNTAG Banyuwangi, using Kooi's house, using a factorial completely randomized design (RAL) method with four replications consisting of two factors: the composition of the growing media and the dose of municipal waste fertilizer.Growth media composition factor (M) consists of 3 treatments, namely: M1 = soil: sand: husk (2: 1: 1); M2 = soil: sand: stem of fern (2: 1: 1); and M3 = soil: sand: cocopeat (2: 1: 1). The composition of municipal solid waste (P) consists of 3 treatments, namely: P1 = composition of municipal solid waste organic fertilizer 25%; P2 = composition of city organic waste 50%; and P3 = composition of urban organic waste 75%. Observation parameters in this study were Plant Height (cm), Number of Leaves, Wet Weight (grams), Number of Tubers, and Tuber Diameter (cm).